Pedagogies of disruption and the challenge of social justice under regimes of neoliberalism - Giroux, Henry A. (Revista Hipótese, 2016)
I argue in this paper in spite of its crucial importance to developing the formative culture necessary to a working democracy, higher education in North America is currently under attack by the apostles of neoliberalism, or what might be called a savage form of casino capitalism. No longer viewed as a source of enlightenment or a democratic public sphere, higher education is devalued because it is seen as a threat neoliberal regimes that fear its role of providing the critical knowledge, skills, and values necessary to produced inspired and critical citizenry. Intent at turning higher education into an adjunct of business culture, the apostles of neoliberalism are waging a campaign to undermine the principles of academic freedom, sacrifice critical pedagogical practice in the name of economic growth, and dismantle the university as a bastion of autonomy, independent thought, and uncorrupted inquiry. At stake in this struggle is a concerted attempt byright-wing extremists and corporate interests to strip the professoriate of any authority, render critical pedagogy as merely an instrumental task, eliminate protections for educators, define students as consumers, produce a form of indebted citizenship, and remove critical reason from any vestige of civic courage, engaged citizenship, and social responsibility. Neoliberalism is the enemy of social justice and if it is to be challenged necessitates that educators from across the globe join in developing a movement for the development of public goods that can work to create alliances to challenge the politics of neoliberalism on a global level.
Keywords: higher education; politics; neoliberalism; civic courage; pedagogy; critical thinking; formative cultures; neoliberalismo